Slag dusts from Kabwe (Zambia): Contaminant mineralogy and oral bioaccessibility. (December 2020) - Ettler, Vojtěch; Štěpánek, David; Mihaljevič, Martin; Drahota, Petr; Jedlicka, Radim; Kříbek, Bohdan; Vaněk, Aleš; Penížek, Vít; Sracek, Ondra; Nyambe, Imasiku
Abstract: The former Pb–Zn mining town of Kabwe in central Zambia is ranked amongst the worst polluted areas both in Africa and in the world. The fine dust particles from the ISF and Waelz slags deposited in Kabwe represent a health risk for the local population. Here, we combined a detailed multi-method mineralogical investigation with oral bioaccessibility testing in simulated gastric fluid (SGF; 0.4 M glycine, pH 1.5, L/S ratio of 100, 1 h, 37 °C) to evaluate the risk related to the incidental dust ingestion. The slag dust fractions contain up to 2610 mg/kg V, 6.3 wt% Pb and 19 wt% Zn. The metals are mainly bound in a slag glass and secondary phases, which formed during the slag weathering or were windblown from nearby tailing stockpiles (carbonates, Fe and Mn oxides, phosphates, vanadates). The bioaccessible fractions (BAFs) are rather high for all the main contaminants, with the BAF values generally higher for the ISF slags than for the Waelz slags: Pb (24–96%), V (21–100%) and Zn (54–81%). The results clearly indicate the potential risks related to the incidental slag dust ingestion. Even when a conservative value of the dust daily intake (100 mg/day) is considered, the daily contaminant intake significantly exceeds the tolerable daily intake limits, especially for Pb ≫ V > Zn. At higher ingestion rates, other minor contaminants (As, Cd) also become a health risk, especially for children. The slag heaps in Kabwe should be fenced to prevent local people entering and should be covered to limit the dust dispersion. Graphical abstract: Image 1 Highlights: Slag dusts from Kabwe (Zambia) contain high levels of contaminants. Metals bound in slag glass, carbonates, oxides and phosphates/vanadates. Bioaccessible fractions up to 96% (Pb), 100% (V) and 81% (Zn). High health risk even under conservative dust intake scenario (100 mg/day).